Double inseminations and treatment of repeat breeders with gonadotropin-releasing hormone - Jeffrey S. Stevenson; Edward P. Call; R.K. Scoby; A.P. Phatak (Kansas Agricultural Experiment Station Research Reports, 1988)
An experiment was conducted in one Kansas and five California dairy herds to determine if double inseminations with and without treatment with 100 µg gonadotropinreleasing hormone (GnRH) would improve conception rates of repeat-breeding dairy cattle (n=723). Both lactating cows and virgin dairy heifers were assigned randomly to treatments as repeat breeders, if they had failed to conceive to at least two previous services. Cows inseminated once and treated with GnRH had the best conception rates (41%), which were higher (P<.OI) than those of cows inseminated once without GnRH treatment (32%) and higher (P<.OI) than those of cows inseminated twice without treatment with GnRH (33%). Cattle bred twice that received the GnRH treatment had intermediate rates (37%). We conclude that treatment of repeat breeders with GnRH at the time of insemination (only one service given according to the am-pm, pm-am rule) improved conception rates.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Gonadotropin-releasing hormone; Conception rates